2017
DOI: 10.1186/s40645-017-0137-6
|View full text |Cite
|
Sign up to set email alerts
|

Potential impact of sea surface temperature on rainfall over the western Philippines

Abstract: The study used a 5 km-resolution regional climate model, the Advanced Research Weather Research and Forecasting Model, to quantify the potential impact of sea surface temperature (SST) west of the Philippines on summer monsoon rainfall on the northwestern coast of the country. A set of control simulations (CTL) driven by ERA-Interim reanalysis data and the monthly National Oceanic and Atmospheric Administration Optimum Interpolation SST dataset was performed for the months of June to August of 1982-2012. A sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 29 publications
1
18
0
Order By: Relevance
“…Thus, we can expect the number of HPE85 days to be sensitive to changes in TC activity in the WNP region; particularly, the northward shift of TC tracks that is linked to the warming of Pacific waters is most affected. In addition, rainfall anomalies were previously shown to be sensitive to SST anomalies to the west of Luzon (Dado and Takahashi 2017). The warming of SST and deepening of the ocean's 26°C isotherm in the SCS (Sun et al 2017) since 2000 may have also contributed to the higher HPE rainfall amount.…”
Section: Discussionmentioning
confidence: 97%
“…Thus, we can expect the number of HPE85 days to be sensitive to changes in TC activity in the WNP region; particularly, the northward shift of TC tracks that is linked to the warming of Pacific waters is most affected. In addition, rainfall anomalies were previously shown to be sensitive to SST anomalies to the west of Luzon (Dado and Takahashi 2017). The warming of SST and deepening of the ocean's 26°C isotherm in the SCS (Sun et al 2017) since 2000 may have also contributed to the higher HPE rainfall amount.…”
Section: Discussionmentioning
confidence: 97%
“…It is generally assumed that one of the most active chemical weathering scenarios globally occurs in the high Himalaya, as a result of the ongoing uplift of the Himalayan-Tibetan Plateau and the heavy rains associated with the Indian-Asian monsoon, which is also linked with the North Pacific monsoon (e.g., Tada and Murray 2016;Clift 2017;Dado and Takahashi 2017). Gaillardet et al (1999) compiled dissolved major ion data in Himalayan Rivers and reported high chemical weathering rates for silicate in the Ganges-Brahmaputra and Ayeyarwady Rivers, and for carbonate in the Yangtze River.…”
Section: Long-term Neutralizing Process Against Enhanced Pcomentioning
confidence: 99%
“…Studies that have highlighted the role of synoptic-local scale interaction in amplifying the extreme events were made for Europe and beyond, too. Apart from the influence of the sea surface temperature (e.g., [27,28]), studies have also focused on the role of orography (including the Carpathian mountains) in the distribution and intensity of precipitation [29][30][31]. Such studies are important in identifying how atmospheric dynamical and thermodynamical processes interact with the particularities of the topography of each region and, as far as possible, in improving the forecast model output.…”
Section: Introductionmentioning
confidence: 99%